MANAJEMEN BELAJAR TUNTAS DALAM PENGELOLAAN MUTU DI SD NEGERI GUNTUR 1 KABUPATEN DEMAK - Rifai Rifai; Suwandi Suwandi; Noor Miyono (Jurnal Manajemen Pendidikan (JMP), 2016)
The background of this research are: 1) student achievement under Criteria Complete Minimal, 2) The results of test scores of children is low, so it does not match the expectations of parents 3) School achievement is low in the academic race, 4) Not achieving the quality of schools maximum as in the vision, mission and objectives of the school that has been set.The objectives of this study are to know the complete learning management and quality management in schools, so that an upgrading in the quality of teaching and learning activities for teachers and school quality improvement of services for parents met.The results showed that: 1) Planning study completed jointly planned at the beginning of the school year at a school meeting. Extra hours of lessons, teacher consultation with headmaster and teachers plan learning activities prepared for mastery learning successfully. 2) Organizing the responsibility of headmaster with the assignment of guiding low grade and high grade guidance. 3) Learning thoroughly carried out in a systematic and planned starting from the preparation of lesson plans, learning activities, assessment, repairment and enrichment. Student involvement in the implementation of high mastery learning, and specifically the sixth grade required for implementation of the study completed two years using the zero hour of learning. 4) Monitoring by the headmaster include oversight of program implementation and supervision of organizing programs consistently. 5) The quality of school graduates performed with competence development, content standards, process standards, educators and education personnel, school facilities and infrastructure, management standards, and implementation of the assessment system.Based on the research results suggested: 1) The headmaster is able to draw up a work program of the school and the ability to provide service quality to parents, 2) Teachers can improve the quality of teaching and learning activities in the classroom and improve the quality of the use of school infrastructure